Jargon Sales & Marketing Hotel Oleh Karyawan Favehoteldi Bali - Lina Sari Tanjung, Dwi; Budiarsa, Made; Seri Malini, Ni Nyoman Luh (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): September 2016, 2016)
The objective of this study is to determine the forms of jargon which used by the employees especially in sales & marketing department in favehotel Bali. The analysis was limited to the jargon form in acronym, abbreviation, word and phrase which speech by the employees of sales & marketing department in favehotel Bali. The data were elaborated on the analysis and presented qualitatively using sosiolinguistics theory. This theory is used to analyze the forms of jargon that found in the employees of sales & marketing department’s speech.The result of the study showed that abbreviation is the most form of jargon that found in the employees of sales & marketing department’s speech in favehotel Bali. The use of jargon is used by employees of sales and marketing department only to create a communication easier. The meaning of jargon itself is not confidential, however not many people can understand its meaning easily if they do not as the group of sales & marketing department. Linguistics patterns in sales & marketing department especially in Favehotel Bali has its own characteristics.
Keywords: jargon, speech, sales & marketing